Rights to land and extractive resources in Tanzania (1/2): The history - Rasmus Hundsbæk Pedersen; Thabit Jacob; Faustin Maganga; Opportuna Kweka (Danish Institute for International Studies (DIIS), 2016)
The extractive industries are becoming more important for Tanzania's economy. Mining and gas production contribute to generating jobs and revenues. However, investments may also pose a threat to existing rights to land, not least because it is the state that owns the sub-soil resources. Generally, it prioritises extraction over the protection of surface land rights. Based on reviews of the extractive sector legislation, the extractive sector literature, and the literature on mainland Tanzania's economic development models, this paper focused on how the rights of different stakeholders have changed over time. It focuses on three different groups of actors, namely smallholders, investors and state actors. It argues that the role of the state in governing investments in the extractive sectors have gradually been strengthened, but that its direct involvement as an investor has waxed and waned. Recently, it has been on its way back in again through state co-ownership in joint-venture operations. This is documented in a second paper, Rights to land and natural resources in Tanzania (2/2): The return of the state.
Keywords: 330; Land; Mining; Petroleum; Gas; Rights; Investments; Tanzania